Decision Support System for Selection of Villages Receiving Plant Seed Assistance in Belitung Regency Using the Simple Additive Weighting (SAW) Method - Aryandita, Muhammad Dwinda Agust; Zahrotun, Lisna (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
The Belitung Regency Regional Food and Agriculture Security Service has a program for distributing plant seed assistance. This program aims to support the Food Security program in Belitung Regency. The problem encountered in the distribution of this assistance was in the selection of prospective beneficiaries which was carried out subjectively and based on activity alone, this resulted in the distribution of assistance not being on target. This study aims to create a decision support system that can select villages as recipients of plant seed assistance using the Simple Additive Weighting method. The stages of this research started with problem identification and research objectives, data collection, data analysis, determining criteria and weighting, then implementing the SAW method, system design, implementation, system testing, and conclusions. The results of this study are a system that can rank selected villages as recipients of plant seeds. With this system, the selection of villages that will receive plant seed assistance from the Food Security and Agriculture Service of the Belitung Regency can be carried out easily and efficiently. Based on tests carried out using Usability Testing with SUS obtaining a value of 81.75 and included in the Acceptable category. Tests using validity carried out also have the same results between manual calculations and calculations from the system so that the results obtained are stated to be valid. The last test was carried out using the Blackbox method which yielded a value of 100% in terms of the functionality of all the features in the system. Looking at the three test results, it can be concluded that the system that has been built is feasible to use.